Dynamic modeling and motion characteristics analysis of variable-length aerial refueling hose-drogue system - ZHAO Wenbi; ZHANG Zehua; ZHAO Ying; YANG Su; QU Yaohong; XI Qingbiao (Xibei Gongye Daxue Xuebao)
During the aerial refueling process, the hose-drogue is disturbed by the complex airflow to occur irregular shaking motion, while the hose-drogue in the impact of the receiver often lead to whipping phenomenon, limiting the success rate and safety of refueling. In order to study the motion characteristics of the refueling hose-drogue system, a variable-length dynamic model of the hose-drogue system was established based on the absolute nodal coordinate method. Considering the damping properties of the hose material, the reel movement of the refueling pod mechanism, and the turbulent and wake vortex in the refueling process, according to the multi-body dynamics theory, the accurate dynamic model of the refueling hose-drogue system under the complex wind field is obtained. By using the finite element analysis software ANSYS and Simulink numerical calculation method, the sinking amount of the drogue under the steady dragging state of the hose is simulated, which shows the accuracy and feasibility of the modeling method proposed in this paper. Meanwhile, the Simulink numerical results of the hose-drogue drag are compared with the public data of NASA. Through numerical simulations, the stable dragging state of the refueling hose at different flight altitudes/speeds are determined, the dynamic characteristics of the hose whipping phenomenon at different docking speeds are analyzed, and the influence of different force measurement feedback points on the whipping suppression effect are verified.